Security event adaptive circulation method and system based on AI algorithm - CHEN ZHUANGZHUANG; MA XIAOHONG; HU XINYUE; NING WEI; LI PENGYU; ZHU HONGJIANG; ZHANG JIANCHENG; WANG WEI; WANG MINGXI; ZHU RUIXIN; LI ZHE; WU XIAOCHEN; et al. (2024)
The invention relates to the field of network security, and provides a security event adaptive circulation method and system based on an AI algorithm. The method comprises the following steps: acquiring a security event, and extracting a related influence factor of the security event; obtaining a current online disposal subject, and extracting related influence factors of the disposal subject; and on the basis of the related influence factors of the security event, the current online disposal subject and the related influence factors of the disposal subject, one or more disposal objects are obtained by adopting an AI selector to serve as a delivery target of the security event, and the disposal subject completes corresponding work and outputs a result of the disposal subject. 本发明涉及网络安全领域，提供了一种基于AI算法的安全事件自适应流转方法及系统。该方法包括，获取安全事件，并提取安全事件的相关影响因子；获取当前在线处置主体，并提取处置主体的相关影响因子；基于安全事件的相关影响因子、当前在线处置主体以及处置主体的相关影响因子，采用AI选择器，得到一个或多个处置对象，作为安全事件的投放目标，由处置主体完成相应工作，输出处置主体的结果。